Statistics for Small States : A Supplement to the World Development Indicators 2009 - World Bank (Washington, DC, 2013)
In 2000 the World Bank made a corporate commitment to organize a small states Forum each year in the context of the International Monetary Fund (IMF) and World Bank annual meetings. The forum is intended to raise the profile of small states issues and provide an opportunity for small state officials to bring their views and ideas to the attention of the international community. Forty-eight World Bank members comprise the small states forum, all but five having populations below 1.5 million. These countries are all included in the World Development Indicators database, but countries with populations of less than one million do not appear in the main tables of the print publication. To better serve this important segment of the Bank's membership and to help highlight the challenges they face, this special supplement to the World Development Indicators (WDI) has been produced, covering critical development factors. The data in this supplement cover 40 members of the small states forum excluding the high-income countries of Bahrain, Brunei Darussalam, Cyprus, Estonia, Iceland, Malta, Qatar, and San Marino.